2006
DOI: 10.4103/0970-4388.22832
|View full text |Cite
|
Sign up to set email alerts
|

Study of trace elements in mixed saliva of caries free and caries active children

Abstract: The present study was carried out to find out the amount of cariogenic and cariostatic trace elements in mixed saliva. It was observed that Cu, Pb, Na showed significant variation in case of one surface as compared to caries free group. Between the non-caries and multiple caries group Cu, Pb, K showed no significant variation Zn showed highly significant variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For caries, previous works in saliva have mainly focused on human-host attributes such as Glucosyltransferase B [23], antimicrobial peptides [24], past caries experience [25], soluble CD14 [26] and trace elements [27], while only a few have exploited individual microbial features, such as specific microbiological counts [28] and microbial nitrate reductase activities [29]. Few global functional analysis and comparison of saliva microbiota function was available, due to (i) the organismal complexity of the microbiota [9] and (ii) the observations that metagenome-sequencing based functional comparison of microbiota can be hampered by sequencing biases [30], the paucity of reference genomes and the small percentage of annotatable reads [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…For caries, previous works in saliva have mainly focused on human-host attributes such as Glucosyltransferase B [23], antimicrobial peptides [24], past caries experience [25], soluble CD14 [26] and trace elements [27], while only a few have exploited individual microbial features, such as specific microbiological counts [28] and microbial nitrate reductase activities [29]. Few global functional analysis and comparison of saliva microbiota function was available, due to (i) the organismal complexity of the microbiota [9] and (ii) the observations that metagenome-sequencing based functional comparison of microbiota can be hampered by sequencing biases [30], the paucity of reference genomes and the small percentage of annotatable reads [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Table (5) shows the differences in salivary total protein and salivary superoxide dismutase between the cariesfree and caries-active groups (DS groups).…”
Section: Resultsmentioning
confidence: 99%
“…According to a study, caries-affected children's salivary total antioxidant capacity increased as compared to caries-free children (4) . Many studies have shown that there are no significant variations in total protein and salivary total antioxidant levels between children with caries and children who do not have caries, regardless of age or gender, with little information about their effects on antioxidants (5,6) .…”
Section: Introductionmentioning
confidence: 99%